Structures on the move: technologies of governance in transcultural encounter - Flüchter, Antje; Richter, Susan (Springer Berlin Heidelberg, 2012)
This book presents a new conceptual framework for comparative and entangled research on transcultural state formation. It examines concepts of statehood to provide conceptual tools to analyze the transcultural appropriation of governmental technologies
Description based upon print version of record
Keywords: Konferenzschrift -- 2011 -- Heidelberg; Geschichte; Kulturvermittlung; Herrschaft; Entwicklung; Staat